Implementasi Groq AI untuk Otomatisasi Feedback pada Website Evaluasi Kinerja Dosen - Kusumastuti, Rajnaparamitha; Oktafiani, Dewi; Dwi Putra, Tommy (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2025)
Lecturer performance evaluation is essential to maintain the quality of higher education, yet traditional methods often lack objectivity and provide limited feedback. This study designed a web-based evaluation system using the Simple Additive Weighting (SAW) method for decision-making, integrated with Groq AI to generate automatic feedback from students. The system was developed with a prototype approach using the Flask framework and tested on 10 courses with a total of 250 randomly selected respondents. Instrument reliability was confirmed using Cronbach’s Alpha (α = 0.84), indicating a high level of reliability. System speed evaluation through 40 trials showed an average processing time of 0.564 seconds. User satisfaction was measured with a 1–4 Likert scale and converted using the Percent of Maximum Possible (POMP), resulting in a 92.4% satisfaction rate. The AI feature successfully provided automated feedback without manual intervention, significantly improving efficiency and effectiveness. These results demonstrate that integrating SAW with Groq AI enhances objectivity, speed, and quality in lecturer performance evaluation.